1997
DOI: 10.1002/(sici)1097-4644(199702)64:2<295::aid-jcb12>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of purified, culture-expanded human mesenchymal stem cells in vitro

Abstract: Human bone marrow contains a population of cells capable of differentiating along multiple mesenchymal cell lineages. Recently, techniques for the purification and culture-expansion of these human marrow-derived Mesenchymal Stem Cells (MSCs) have been developed. The goals of the current study were to establish a reproducible system for the in vitro osteogenic differentiation of human MSCs, and to characterize the effect of changes in the microenvironment upon the process. MSCs derived from 2nd or 3rd passage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
958
3
20

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,299 publications
(1,050 citation statements)
references
References 60 publications
42
958
3
20
Order By: Relevance
“…The classic osteogenic differentiation of MSCs in different tissues requires distinct signals (Jaiswal et al, 1997;Pittenger et al, 1999). It has been demonstrated that only one-third of initial adherent bone marrow-derived MSC colonies are pluripotent and capable of differentiating into osteoblastic, chondrocytic and adipocytic cell lineages, while the majority of MSCs exhibits a bilineage (osteo/chondro) or unilineage (osteo) potential.…”
Section: Plasticity and The Differentiation Potential Of Mscsmentioning
confidence: 99%
“…The classic osteogenic differentiation of MSCs in different tissues requires distinct signals (Jaiswal et al, 1997;Pittenger et al, 1999). It has been demonstrated that only one-third of initial adherent bone marrow-derived MSC colonies are pluripotent and capable of differentiating into osteoblastic, chondrocytic and adipocytic cell lineages, while the majority of MSCs exhibits a bilineage (osteo/chondro) or unilineage (osteo) potential.…”
Section: Plasticity and The Differentiation Potential Of Mscsmentioning
confidence: 99%
“…This range of concentrations of Dex has been shown to be effective for the osteogenic differentiation of MSCs. [41,50] It is known that ALP, a cell surface glycoprotein, is an early marker of osteogenic differentiation. [47,51] To confirm the osteogenic differentiation of RBMSCs exposed to Dex-loaded CMCht/PAMAM dendrimer nanoparticles, we carried out an ALP staining (Fig.…”
Section: In-vitro Osteogenic Differentiation Of Rbmscs Exposed To Thementioning
confidence: 99%
“…We and others have shown previously the ability to modulate the phenotype of human bone marrow stromal Âźbroblasts into a variety of cell and tissue types (Caplan, 1991;Jaiswal et al, 1997;Horwitz et al, 1999;Oreffo et al, 1997;Pittenger et al, 1999). MagniÂźcation  100. c: Osteocalcin expression in human bone marrow cells as detected by immunocytochemistry using monoclonal antibody, OS 35, which shows speciÂźc reactivity with osteocalcin in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the isolation and characterization of such stem cells has been hampered by the lack of speciÂźcally reactive antibodies and the very low incidence of these cells. Current approaches have centered on the isolation and expansion of these early progenitors from marrow Âźbroblast populations Jaiswal et al, 1997;Kadiyala et al, 1997). Recent animal and human studies indicate that mesenchymal stem cell therapy may be a realistic therapeutic target for a variety of skeletal, muscular, and haemopoietic diseases (Prockop, 1997;Baltzer et al, 1999;Marx et al, 1999;Oyama et al, 1999;Horwitz et al, 1999).…”
mentioning
confidence: 96%